Localised prostate cancer in elderly men aged 80–89 years, findings from a population‐based registry. (May 2018) - Vatandoust, Sina; Kichenadasse, Ganessan; O'Callaghan, Michael; Vincent, Andrew D.; Kopsaftis, Tina; Walsh, Scott; Borg, Martin; Karapetis, Christos S.; Moretti, Kim
Abstract : Objectives: To investigate the rate of prostate cancer‐specific mortality (PCSM) and disease characteristics in patients diagnosed with localised prostate cancer at age 80–89 years in comparison with men diagnosed at age 70–79 years. Patients and Methods: This is a retrospective study of data from the South Australian Prostate Cancer Clinical Outcomes Collaborative (SA‐PCCOC). Included were men diagnosed between 2005 and 2014, aged ≥70 years with no evidence of metastatic disease at presentation. Propensity score matching and competing risk Fine and Grey regression were used to assess the chance of treatment (curative vs non‐curative) and treatment effect on PCSM. Results: Of the 1 951 eligible patients, 1 428 (76%) were aged 70–79 years and 460 (24%) were aged 80–89 years at diagnosis, with a median (interquartile range) age of 74 (72–76) and 83 (81–85) years, respectively. The 80–89 years group had higher Gleason scores and Prostate Specific Antigen (PSA) values (all P < 0.001) in comparison with the younger group. The 80–89 years group were less likely to be treated with curative treatment (odds ratio 0.12, 95% confidence interval 0.09–0.16; P < 0.001). The proportion of deaths attributable to prostate cancer was similar in both groups: 73 of 263 deaths (28%) in the 80–89 years group vs 97 of 310 deaths (31%) in the 70–79 years group. The risk of PCSM in individuals treated with curative intent was reduced in both groups. Conclusions: The proportion of prostate cancer deaths was similar in both groups. These findings support carefully selected individualised management of elderly patients diagnosed with localised prostate cancer.